The Interplay of HIV-1 and Macrophages in Viral Persistence - Hendricks, Chynna M.; Cordeiro, Thaissa; Gomes, Ana Paula; Stevenson, Mario (Frontiers in Microbiology, 2021)
HIV-1 has evolved mechanisms to evade host cell immune responses and persist for lifelong infection. Latent cellular reservoirs are responsible for this persistence of HIV-1 despite the powerful effects of highly active antiretroviral therapies (HAART) to control circulating viral load. While cellular reservoirs have been extensively studied, much of these studies have focused on peripheral blood and resting memory CD4+ T cells containing latent HIV-1 provirus; however, efforts to eradicate cellular reservoirs have been stunted by reservoirs found in tissues compartments that are not easily accessible. These tissues contain resting memory CD4+ T cells and tissue resident macrophages, another latent cellular reservoir to HIV-1. Tissue resident macrophages have been associated with HIV-1 infection since the 1980s, and evidence has continued to grow regarding their role in HIV-1 persistence. Specific biological characteristics play a vital role as to why macrophages are latent cellular reservoirs for HIV-1, and in vitro and in vivo studies exhibit how macrophages contribute to viral persistence in individuals and animals on antiretroviral therapies. In this review, we characterize the role and evolutionary advantages of macrophage reservoirs to HIV-1 and their contribution to HIV-1 persistence. In acknowledging the interplay of HIV-1 and macrophages in the host, we identify reasons why current strategies are incapable of eliminating HIV-1 reservoirs and why efforts must focus on eradicating reservoirs to find a future functional cure.